The professional learning community. A fulcrum of change. (Kairaranga, 2008)
Paralleling the accelerating pace of educational change in the last two decades has been the development of a professional learning community (PLC) in schools. Characterised by teacher collaboration and a spirit of enquiry, the PLC represents a response to change and an opportunity to benefit teachers, students and schools, using an approach most suited to adults. The paper undertakes a literature review of various aspects of the PLC: attributes; evolution; benefits; and measurement of the PLC.